2010
DOI: 10.1007/s00468-010-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl on leaf H+-ATPase and the relevance to salt tolerance in two contrasting poplar species

Abstract: During a 30-day period of increasing salinity, we examined the effects of NaCl on leaf H? -ATPase and salinity tolerance in 1-year-old plants of Populus euphratica Oliv. (salt resistant) and P. popularis 35-44 (P. popularis) (salt sensitive). Electron probe X-ray microanalysis of leaf mesophyll revealed that P. euphratica had a higher ability to retain lower NaCl concentrations in the cytoplasm, as compared to P. popularis. The sustained activity of H ? pumps (by cytochemical staining) in salinised P. euphrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…; Ma et al . ) and mediating seasonal signals in cambial cells of poplars (Arend et al . ), scarce information is available on transcriptional regulation of genes encoding PM H + ‐ATPases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ma et al . ) and mediating seasonal signals in cambial cells of poplars (Arend et al . ), scarce information is available on transcriptional regulation of genes encoding PM H + ‐ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…× canescens may lead to higher activities of PM H + -ATPases and thus, higher H + release, driving higher Cd 2+ absorption rates in EMs. Although the roles of PM H + -ATPases have been documented in uptake of NH4 + and NO3 − , cellular Na + extrusion (Beritognolo et al 2007;Ma et al 2010) and mediating seasonal signals in cambial cells of poplars (Arend et al 2002), scarce information is available on transcriptional regulation of genes encoding PM H + -ATPases. Down-regulated transcripts of genes coding PM H + -ATPases have been reported for leaves of Po.…”
Section: Ems Have No Effects On Spatial Variation Pattern Of CD 2+ Upmentioning
confidence: 99%
“…Salt induced an oxidative stress in chloroplast and mitochondria of pea leaves [28][29][30]34]. In poplars, great buildup of Na + and Cl À in chloroplasts may directly cause ion toxicity and induce the subsequent oxidative stress [26,38]. X-ray microanalysis results showed that the inability for the restriction of Na + entry into the chloroplasts leads to an uncontrolled oxidation in Populus popularis [26,38].…”
Section: Introductionmentioning
confidence: 99%
“…In poplars, great buildup of Na + and Cl À in chloroplasts may directly cause ion toxicity and induce the subsequent oxidative stress [26,38]. X-ray microanalysis results showed that the inability for the restriction of Na + entry into the chloroplasts leads to an uncontrolled oxidation in Populus popularis [26,38]. Salt-resistant plants may maintain ROS homeostasis through limiting ROS production by a protective salt partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this suggestion transgenic poplars that were more Cd 2+ tolerant by overexpression of γ-glutamylcysteine synthetase, showed upregulated transcript levels of VHA1.1 , HA2.1 and AHA10.1 and a high Cd 2+ uptake rate (He et al, 2015). The PM H + -ATPases maintain a H + gradient across the membrane to promote active transport of essential elements across the PM (Beritognolo et al, 2007; Ma et al, 2010; Sun et al, 2010; Luo et al, 2013). Increased H + -pumping activities have been well characterized in arbuscular mycorrhizal associations (Ramos et al, 2005; Rosewarne et al, 2007) and in ectomycorrhizal associations formed by Paxillus involutus (strains MAJ and NAU) with Populus × canescens (Li J. et al, 2012).…”
Section: Introductionmentioning
confidence: 99%